EFEKTIFITAS BAKTERI ENDOFIT DAN PENAMBAHAN INDOLE ACETIC ACID (IAA) DALAM MENINGKATKAN PERTUMBUHAN TANAMAN PADI Oryza sativa L. - Aria Rizki Ramadhan; Oedjijono Oedjijono; Ratih Dewi Hastuti (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
Rice plant needs essential and non-essential nutrients to grow. However, the use of inorganic fertilizers may affect the soil microbe community which expected to increase the availability of nutrients for both plants and microbes, a condition that could control several types of diseases. Many efforts were made to find alternative fertilizer which environmentally friendly, for instance by exploiting microorganisms such as endophytic bacteria associated with plant tissue or seed plant cell. This research aimed to determine the effect of endophytic bacteria, the concentration of IAA, and the combination of endophytic bacteria with a concentration of IAA, on the growth of rice plant. This research was conducted at the Laboratory of Soil Biology, The Soil Research Institute located in Cimanggu Bogor from December 2015 to February 2016. This research was a Completely Randomized Design (CRD) with two factors, i.e., the inoculant of endophytic bacteria (2.2 KT, KR 6, and I CM), and the concentration of IAA (0, 0.01, 0.1, 0.5, and 1 ppm). Three replicates were applied for each treatment of the inoculant combined with different doses of IAA. The variety of rice plants tested were Inpari 13 and IR 64. The potential test has been applied to determine the factor with the highest yield of the rice plant growth. The parameters observed were the height of the rice plant, the length of the rice plant roots, and the total weight of the plant including root. The results showed the inocula of endophytic bacteria alone had no effect to increase growth for both IR 64 and Inpari 13 rice variety. The IAA concentration of 0.1 ppm was able to increase the height of rice plant and the length of rice plant root for both IR 64 rice plant and Inpari 13. The combined treatment of KR 6 bacterial inoculum with 1 ppm of IAA concentration was effectively promoted rice plant growth for both IR 64 and Inpari 13.